Evaluation of the Morphology, Yield and Content of Beta-carotene Sweet Potato (Ipomoea batatas L.) Orange Flesh Results of Beta-2 Female Broodstock Assembly - Hardiane Ketut; Dewi Ratna; Maulida Desi; Wahyudi Anung (Biology, Medicine, & Natural Product Chemistry, 2026)
Sweet potato (Ipomoea batatas L.) is a functional food commodity that has the potential to support food diversification because it has a high content of beta-carotene as a provitamin A and a natural antioxidant. This study aimed to evaluate the morphological character, yieldability, and content of beta-carotene, dry matter, and sugar content in orange fleshy sweet potato clones assembled by female broodstock Beta-2. The study used a single-factor Group Random Design (RAK) with six clones, namely BOP 36, BOP 42, BOP 73, BOP 77, Beta-2, and Sari, which was repeated four times so that 24 experimental units were obtained. The data was analyzed using Analysis of Variance (ANOVA) followed by a BNT test of 5%. The results showed that there were significant differences in morphological characteristics, productivity, beta-carotene content, dry matter, and sugar content between clones. The BOP 73 clone produced the highest productivity with an average tuber weight of 234.37 g/plant, followed by BOP 36 of 205.87 g/plant. The two clones also have a higher content of beta-carotene, dry matter, and sugar content than the Beta-2 and Sari comparison clones. The BOP 36 clone which has a deep orange tuber has the potential to be developed as a new superior clone that supports food diversification, improving the quality of community nutrition, and strengthening food security through the provision of productive and provitamin A-rich local food.